Modern environmental legal order: theoretical foundation and applied problems solving - Makarova, Tamara I.; Zhloba, Albert A.; Lizgaro Viсtoria E.; Moroz, Oleg V. (Journal of the Belarusian State University. Law, 2025)
The conceptual foundations of the modern environmental legal order and its organisational support are studied. It is proved that the foundation of the environmental legal order is the ratio of imperativeness and optionality. It is proposed to include in the system of environmental legal order the regime of the national ecological network, the unification of legal protection of the environment and protection of natural resources around the concept «environmental support of economic activity», imposition of liability for failure to comply environmental and legal regulations. Proposals for improving the legal regulation of environmental relations are formulated.